2004
DOI: 10.1007/s00424-003-1221-x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular nucleotides and polyamines inhibit the Ca 2+ -activated cation channel TRPM4b

Abstract: TRPM4b (in contrast to the short splice variant TRPM4a) is a Ca(2+)-activated but Ca(2+)-impermeable cation channel. We have studied TRPM4 currents in inside-out patches. Supramicromolar Ca(2+) concentrations applied at the inner side, [Ca(2+)](i), activated TRPM4 with an EC(50) value of 0.37 mM, a value that is much higher than that of whole-cell currents. Current amplitudes decreased above 1 mM [Ca(2+)](i), (IC(50) 9.3 mM). Sr(2+) but not Ba(2+)could partially substitute for Ca(2+). ATP, ADP, AMP and AMP-PNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(114 citation statements)
references
References 23 publications
4
109
0
1
Order By: Relevance
“…Cytosolic ATP has divergent effects on TRPM4 activity: free ATP but not the Mg 2+ -chelated ATP (ATP-Mg) can inhibit the channel 15 , while exposing desensitized TRPM4 to ATP-Mg can alleviate desensitization, thereby increase channel conductance 13,16 . To define the role of ATP binding at NBD, we mutated the three aromatic residues at the ATP binding site to alanine, individually.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytosolic ATP has divergent effects on TRPM4 activity: free ATP but not the Mg 2+ -chelated ATP (ATP-Mg) can inhibit the channel 15 , while exposing desensitized TRPM4 to ATP-Mg can alleviate desensitization, thereby increase channel conductance 13,16 . To define the role of ATP binding at NBD, we mutated the three aromatic residues at the ATP binding site to alanine, individually.…”
Section: Resultsmentioning
confidence: 99%
“…Because the ATP specificity in TRPM4 is mainly defined by the adenine moiety of the nucleotide (Fig. 2c), ADP and AMP can also bind and inhibit TRPM4 15 . The basic residues surrounding the ATP site likely stabilize the negatively charged triphosphate group and may prevent the binding of ATP-Mg.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4A). After desensitization, we tested the effect of 10 M free ATP, as reported (10). Steady-state currents were significantly inhibited by ATP (Fig.…”
Section: Properties Of Trpm4 Channels Expressed In Cosm6 Cellsmentioning
confidence: 92%
“…These channels are structurally distant from the Kir family, but intriguingly, TRPM4, similar to Kir6.2, is sensitive to inhibition by cytoplasmic ATP in the micromolar range (10). It has been reported that, after traumatic brain or spinal cord injury, or ischemia after stroke, SUR1 is up-regulated in neurovascular cells such as reactive astrocytes and endothelial cells at the site of injury (11,12).…”
mentioning
confidence: 99%